2020
DOI: 10.3390/ijerph17238958
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Metabolic Syndrome and Related Factors among the Community-Dwelling Indigenous Population in Taiwan

Abstract: The aim of this study was to conduct a community-based study with a view to construct a detailed analysis about metabolic syndrome and the related risk factors of the indigenous population. This was an observational, population-based and cross-sectional study that was conducted in remote villages of an indigenous community in northern Taiwan between 2010 and 2013. A total of 586 participants, 275 men and 311 women, were eligible for analysis. The participants underwent a questionnaire survey that included demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…This study is one of the few to have investigated MetS and its related factors among hospital employees with a longitudinal cohort. The results of the GEE model showed that increasing age, higher BMI, and higher WBC, ALT, and UA levels were associated with a significantly elevated risk of MetS, which is similar to previous findings [ 1 , 6 , 21 , 27 , 28 ]. However, Ho et al, Shafique et al, and Rhee et al used a cross-sectional design [ 6 , 20 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study is one of the few to have investigated MetS and its related factors among hospital employees with a longitudinal cohort. The results of the GEE model showed that increasing age, higher BMI, and higher WBC, ALT, and UA levels were associated with a significantly elevated risk of MetS, which is similar to previous findings [ 1 , 6 , 21 , 27 , 28 ]. However, Ho et al, Shafique et al, and Rhee et al used a cross-sectional design [ 6 , 20 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…The causes of adverse metabolic outcomes have been posited to include a causal link between metabolic regulation and the molecular function of the circadian rhythm [ 16 ]. Previous research indicated that individual characteristics, such as shift work, chronic disease, family history [ 17 ], higher body mass index (BMI) [ 13 , 18 ], and unhealthy behaviours [ 19 , 20 , 21 ], are associated with higher rates of MetS. In summary, past studies pointed out that being male, being a middle-aged or older adult, having chronic diseases, having greater family histories, participating in shift work, smoking cigarettes, drinking alcohol, and chewing betel nuts were correlated with MetS [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 20 , 22 , 23 , 26 , 32 , 37 , 45 , 46 , 48 , 51–53 Even though a recent study among Taiwanese adults also showed a lower risk in men than women, the results were not statistically significant. 54 The significant sex-age interaction on MS has also been confirmed in some studies. 10 , 11 , 18 , 22 , 28 , 32 , 33 , 38 , 40 Like our results, age was directly associated with the prevalence of MS in Taiwanese 10 , 51 , 52 , 54 , 55 and other populations.…”
Section: Discussionmentioning
confidence: 63%
“… 54 The significant sex-age interaction on MS has also been confirmed in some studies. 10 , 11 , 18 , 22 , 28 , 32 , 33 , 38 , 40 Like our results, age was directly associated with the prevalence of MS in Taiwanese 10 , 51 , 52 , 54 , 55 and other populations. 52 , 53 , 56 , 57 However, unlike our study, the prevalence in women was initially lower than in men but later increased rapidly, surpassing that in men, with a crossover effect occurring between both sexes at 60–69 years.…”
Section: Discussionmentioning
confidence: 63%